Synthesis of sulfur karrikin bioisosteres as potential neuroprotectives - Pošta, Martin; Zima, Václav; Poštová Slavětínská, Lenka; Matoušová, Marika; Beier, Petr (Beilstein Journal of Organic Chemistry, 2022)
The only known sulfur-containing karrikin, 3-methyl-2H-thiopyrano[3,4-b]furan-2-one, has been recently identified as an extremely efficient neuroprotective butenolide. Herein, we report the targeted synthesis of this compound as well as new synthetic protocols toward a class of compounds derived from 2H-furo[2,3-c]pyran-2-ones (karrikins) via bioisosteric exchange of oxygen with sulfur. In particular, we present synthetic procedures toward bioisosteres of karrikins with one or two sulfur heteroatoms incorporated into the core backbone together with evaluation of their biological activity in inhibition of acetylcholinesterase.
Keywords: acetylcholinesterase; butenolides; karrikin; sulfur